2002
DOI: 10.1084/jem.20020542
|View full text |Cite
|
Sign up to set email alerts
|

I-PLA2 Activation during Apoptosis Promotes the Exposure of Membrane Lysophosphatidylcholine Leading to Binding by Natural Immunoglobulin M Antibodies and Complement Activation

Abstract: Deficiency of serum immunoglobulin (Ig)M is associated with the development of a lupus-like disease in mice. Recent studies suggest that classical complement components facilitate the clearance of apoptotic cells and that failure to do so predisposes mice to lupus. Since IgM is a potent activator of the classical complement pathway, we examined IgM binding to dying cells. IgM, but not IgG, bound to apoptotic T cells through the Fab′ portion of the antibody. Exposure of apoptotic cell membranes to phospholipase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
183
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(196 citation statements)
references
References 54 publications
9
183
2
Order By: Relevance
“…16 'Natural' IgM has also been shown to have an enhanced ability to bind to apoptotic cells, and to promote phagocytosis. 12 These observations differed from ours (as well as those of others 33,34 ); normal human IgM was included as a control in all our experiments, but was never found to bind to an extent equivalent to RN86. The fact that our experiments were conducted at much lower concentrations of antibody as well as the differing protocols employed for the induction of apoptosis may account for the discrepancy.…”
Section: Reactivity Of the Immunizing Antibody (Rn86) Is Shown For Recontrasting
confidence: 88%
See 1 more Smart Citation
“…16 'Natural' IgM has also been shown to have an enhanced ability to bind to apoptotic cells, and to promote phagocytosis. 12 These observations differed from ours (as well as those of others 33,34 ); normal human IgM was included as a control in all our experiments, but was never found to bind to an extent equivalent to RN86. The fact that our experiments were conducted at much lower concentrations of antibody as well as the differing protocols employed for the induction of apoptosis may account for the discrepancy.…”
Section: Reactivity Of the Immunizing Antibody (Rn86) Is Shown For Recontrasting
confidence: 88%
“…Interestingly, serum IgM knockout animals demonstrate an SLE-like phenotype, 11 and some components of 'natural' IgM antibodies have been shown to bind apoptotic cells and may play an important role in clearance of cellular debris. 12 This study was conceived to investigate the physiological significance and immunological consequences of an early human autoimmune response specifically directed against apoptotic cells. Towards this end, an IgM [k] human monoclonal antibody specific to cell antigen(s) revealed at the late stages of apoptosis was generated from B cells isolated from an SLE patient.…”
Section: Introductionmentioning
confidence: 99%
“…91 These effects are dependent on different receptors as well as cell types, but not yet fully understood. LPC can also act as an indirect eat-me signal by promoting the LPC-dependent binding of IgM to apoptotic, 92 late apoptotic 93,94 and necrotic cells, 95 ultimately leading to clearance. LPC-IgM-dependent binding to different apoptotic and necrotic states may serve as a backup to normal recognition in situations where large numbers of cells are undergoing apoptosis.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…38 The remodelled membranes generates phagocytic attraction signals to allow correct disposal of the cell remnants created resulting from the apoptotic process. 22,[39][40][41] While not required within apoptotic neurons, complete loss of PLA2G4A and PLA2G2A abolishes inflammation following central nervous system (CNS) injury, and reduces neuronal apoptosis. 19 Studies have shown how PLA2G4A is expressed in adjacent glial cells postinjury, but not within apoptotic neurons.…”
Section: Memory Formation (Long-term Potentiation)mentioning
confidence: 99%